Evolving Chemotherapy Free Regimens for Acute Promyelocytic Leukemia - Kulkarni, Uday; Mathews, Vikram (Frontiers in Oncology, 2021)
With the treatment advances over the last 3 decades, acute promyelocytic leukemia (APL) has evolved from being the most malignant form of acute leukemia to a leukemia with excellent long term survival rates. In the present review, we have summarized data leading to the development of the currently used treatment regimens for APL, which incorporate either none or minimal chemotherapeutic drugs. We have discussed the historical aspects of APL treatment along with the challenges associated with chemotherapy based approaches and our experience with the use of single agent arsenic trioxide (ATO) which was one of the first successful, non-chemotherapy approaches used for APL. Subsequently, we have reviewed the data from major clinical trials in low-intermediate risk APL and high risk APL which guide the current clinical practice in APL management. With accumulating data on oral ATO, we postulate that the treatment for low-intermediate risk APL will be a completely oral ATO+ATRA regimen in the future. While for high-risk APL, we believe that minimal anthracycline use with ATO+ATRA might become the standard of care soon. A number of promising non-chemotherapy drugs with pre-clinical data would merit clinical testing in the high risk and relapsed setting, with potential to translate to a complete oral chemotherapy free combination regimen in combination with ATO and ATRA.